The mitochondrial cytochrome c N-terminal region is critical for maturation by holocytochrome c synthase. - Stevens, J; Zhang, Y; Muthuvel, G; Sam, K; Allen, J; Ferguson, S (2011)
The covalent attachment of heme to mitochondrial cytochrome c is catalysed by holocytochrome c synthase (HCCS, also called heme lyase). How HCCS functions and recognises the substrate apocytochrome is unknown. Here we have examined HCCS recognition of a chimeric substrate comprising a short mitochondrial cytochrome c N-terminal region with the C-terminal sequence, including the CXXCH heme-binding motif, of a bacterial cytochrome c that is not otherwise processed by HCCS. Heme attachment to the chimera demonstrates the importance of the N-terminal region of the cytochrome. A series of variants of a mitochondrial cytochrome c with amino acid replacements in the N-terminal region have narrowed down the specificity determinants, providing insight into HCCS substrate recognition.